Management of Formal Early Education Based on Islamic Boarding Schools in Improving Santri Competence - Moh. Asyari Akbar; Hendi Suhendraya Muchtar; Usep Kosasih; Dinny Mardiana (Journal of Islamicate Studies, 2022)
There is concern over the scarcity of cadres of ulama (mutafaqqih fiddin) due to the low interest of students in entering pesantren. This is due to the public's perception of education in Islamic boarding schools that cannot continue to a higher level of education. The Ministry of Religion of the Republic of Indonesia responded to this problem by opening Formal Diniyah Education (PDF) in Islamic boarding schools as a constructive step in the world of education. This research method uses descriptive qualitative. The results of this study are that the management of PDF applies the leadership pattern as a hotline between students and all parties. This pattern of leadership also acts as a supervisor for student activities at school and in Islamic boarding schools. So that both goals can be achieved. This PDF management effectively uses a scientific approach to the 2013 curriculum process by implementing a learning integration process every semester. The scientific approach refers to the realm of cognitive, affective, and skill competencies.